Self-Assembly of Amphiphiles for the Modular Formation of Catalysts and Sensors - Ren, Zhijun (Auckland University of Technology, 2023)
This thesis describes a new strategy for the formation and optimisation of cooperative catalysts utilising reversible hydrophobic interactions. This involves the self-assembly of pre-catalyst amphiphiles into vesicular structures, where the catalytically active head groups are brought into close proximity to work in a synergistic manner. These proof-of-concept studies focused on the combination of two pre-catalyst amphiphiles, C16TACN 20 and C16Gua 23. The two amphiphiles were self-assembled in 20% DMSO solution, resulting in a significant enhancement in the rate of hydroxypropyl p-nitrophenyl phosphate (HPNPP) cleavage. One of the key advantages of this self-assembled system is its modular nature, which allows the catalyst to be rapidly optimized by changing the composition of the self-assembled system. We were able to demonstrate this concept by modifying the ratio of C16TACN 20 to C16Gua 23, arriving at an optimised system consisting of two C16Gua 23 units for every single C16TACN 20 unit. To gain insight into the self-assembly process and the composition of the vesicular structures formed in situ, we synthesised fluorescent analogues of our pre-catalytic amphiphiles C16TACN 20 and C16Gua 23. The idea was that changes in FRET intensity could be used to follow the self-assembly of different amphiphiles, and allow insight into the dynamic changes that occur when additional amphiphiles are added in situ. During investigation of the fluorescent properties of the fluoro-amphiphiles, we observed that C12-I-Coum-TACN 54 demonstrated unexpected turn-on fluorescence in the presence of Zn2+ and dimethyl phosphate. We propose that the turn-on fluorescence is due to the triple interplay between photoinduced electron transfer (PET), chelation-enhanced fluorescence (CHEF) and aggregation induced emission (AIE) effects. Control studies demonstrated the importance of self-assembly for the observed properties, as the shorter chain analogues did not display significant enhancement of fluorescence upon the addition of dimethyl phosphate. We show that C12-I-Coum-TACN 54 possesses high selectivity for dimethyl phosphate over ATP and pyrophosphate, which is highly unusual given the higher charge density of the latter polyatomic anions. Most literature examples of phosphate sensors target the detection of ATP and pyrophosphate, and therefore we believe our unique observations could lead to the development of sensors selective for dialkyl phosphates, which have applications for the detection of pesticides.